Tafsir sufi: Kajian analitikal Terhadap kitab tafsira al-Bahr al-Madid fi tafsir al-Quran al-Majid oleh Ibn `Ajibah (1160 -1224 H) / Firdaus Sulaiman - Firdaus , Sulaiman (2016)
This research relates to the exegesis of the Holy Quran which was written by a leading Sufi personality from Morocco by the name of Syeikh Ahmad Ibn Muhammad Ibn al-Mahdi Ibn Ajibah al-Hasani or better known as Syeikh Ibn „Ajibah. Syeikh Ibn „Ajibah lived in the 12th Hijriyah (18th Massihiyyah) Century and was a renowned expert in the field of the Holy Quran exegesis, interpretation, the Hadith, Jurisprudence and Sufism. Through this research, an attempt has been made to clarify the interpretation methodology which was applied and used by Syeikh Ibn „Ajibah and his views in relation to Sufism in his written work, al-Bahr al-Madid fi Tafsir al-Quran al-Majid. It has also been found through this research that Syeikh Ibn „Ajibah has interpreted the entire verses of the Holy Quran by combining both interpretational methodologies which are literal (external) and spiritual (internal) in nature. His literal interpretation follows the normal or routine approach generally adopted by most interpreters. Of notable interest was that Syeikh Ibn „Ajibah frequently issued narrations where its original source was ambiguous, particularly narrations related to tales of the Israelites. With regards to his spiritual interpretation, it was deemed to be based on the Isyari (symbolic) method. The interpretations are expressed in a symbolic manner where such symbols contain clarifications over verses of the Holy Quran from a Sufi perspective. These clarifications are linked to Sufism concepts and doctrines which have been in the past expressed by leading Sufi figures, whether from amongst the Sufi practitioners as indeed Sufi philosophers. Syeikh Ibn „Ajibah‟s book al-Bahr al-Madid fi Tafsir al-Quran al-Majid is therefore regarded as a compilation of the Holy Quran‟s interpretation comprising both the viewpoints of Sufi practitioners and philosophers.